The ALMaQUEST Survey – II. What drives central starbursts at z ∼ 0?. Issue 4 (10th January 2020) - Ellison, Sara L; Thorp, Mallory D; Pan, Hsi-An; Lin, Lihwai; Scudder, Jillian M; Bluck, Asa F L; Sánchez, Sebastian F; Sargent, Mark
ABSTRACT: Starburst galaxies have elevated star formation rates (SFRs) for their stellar mass. In Ellison et al., we used integral field unit maps of SFR surface density (ΣSFR ) and stellar mass surface density (Σ⋆ ) to show that starburst galaxies in the local universe are driven by SFRs that are preferentially boosted in their central regions. Here, we present molecular gas maps obtained with the Atacama Large Millimeter Array (ALMA) observatory for 12 central starburst galaxies at z ∼ 0 drawn from the Mapping Nearby Galaxies at Apache Point Observatory (MaNGA) survey. The ALMA and MaNGA data are well matched in spatial resolution, such that the ALMA maps of molecular gas surface density ($Σ _{\rm H_2}$ ) can be directly compared with MaNGA maps at kpc-scale resolution. The combination of $Σ _{\rm H_2}$, Σ⋆ and ΣSFR at the same resolution allow us to investigate whether central starbursts are driven primarily by enhancements in star formation efficiency (SFE) or by increased gas fractions. By computing offsets from the resolved Kennicutt-Schmidt relation ($Σ _{\rm H_2}$ versus ΣSFR ) and the molecular gas main sequence (Σ⋆ versus $Σ _{\rm H_2}$ ), we conclude that the primary driver of the central starburst is an elevated SFE. We also show that the enhancement in ΣSFR is accompanied by a dilution in O/H, consistent with a triggering that is induced by metal poor gas inflow. These observational signatures are found in both undisturbed (9/12 galaxies in our sample) and recently merged galaxies, indicating that both interactions and secular mechanisms contribute to central starbursts.